Simulated moving bed adsorptive reactor - Leão, C.P. (2010)
The Simulated Moving Bed (SMB) technology is a mature one with above 100 applications in chemical industry (UOP Sorbex processes). Now it is finding applications in fine chemistry and pharmaceuticals (chiral separations). In this work, separation is coupled with reaction. The test system is enzymatic inversion of sucrose coupled with glucose/fructose separation using Ca2+ resin as adsorbent. Modeling, simulation and operation of a pilot plant is addressed.